E-Government Program to Enhance Digital Administration in Borobudur Tourism Village - Permana, Dian Fithra; Oktarina, Nina; Wijaya, Angga; Anggraeni, Liza Dwi; Maulida, Syaefa Habsyah Nur (Journal of Community Empowerment, 2024)
In the current era, digital transformation is essential for accelerating document processing and administrative services, enhancing community engagement in village administration processes, and strengthening competitiveness as a tourist village through e-government. Borobudur Tourist Village, a UNESCO World Heritage Site, still requires improvements in administrative efficiency due to suboptimal village administration. The village faces challenges in managing administrative services that demand automation. This community service initiative involved local government officials and business operators in the Borobudur Tourist Village area. The program employed a phased approach, including training sessions on using e-government programs. The web-based e-government platform was developed to enhance document processing, increase community participation, and bolster the competitiveness of the tourist village. The results demonstrated high enthusiasm among participants and significant positive impacts on simplifying administrative services. With the successful implementation of this program, Borobudur Tourist Village has not only improved services for residents and tourists but also established itself as a model for other tourist villages. Digital transformation is expected to contribute to more transparent, responsive, and sustainable management, reinforcing Borobudur Tourist Village's position as a competitive tourist destination.